Dose-dependent effects of dietary nitrate on the oxygen cost of moderate-intensity exercise: Acute vs. chronic supplementation - Wylie, Lee J.; Ortiz de Zevallos, Joaquin; Isidore, Taro; Nyman, Lara; Vanhatalo, Anni; Bailey, Stephen J.; Jones, Andrew M. (Nitric oxide, 2016)
To investigate whether chronic supplementation with a low or moderate dose of dietary nitrate (NO3−) reduces submaximal exercise oxygen uptake (V˙O2) and to assess whether or not this is dependent on acute NO3− administration prior to exercise. Following baseline tests, 34 healthy subjects were allocated to receive 3 mmol NO3−, 6 mmol NO3− or placebo. Two hours following the first ingestion, and after 7, 28 and 30 days of supplementation, subjects completed two moderate-intensity step exercise tests. On days 28 and 30, subjects in the NO3− groups completed the test 2 h post consumption of a NO3− dose (CHR + ACU) and a placebo dose (CHR). Plasma nitrite concentration ([NO2−]) was elevated in a dose-dependent manner at 2 h, 7 days and 28–30 days on the CHR + ACU visit. Compared to pre-treatment baseline, 6 mmol NO3− reduced the steady-state V˙O2 during moderate-intensity exercise by 3% at 2 h (P = 0.06), 7 days and at 28–30 days (both P < 0.05) on the CHR + ACU visit, but was unaffected by 3 mmol NO3− at all measurement points. On the CHR visit in the 6 mmol group, plasma [NO2−] had returned to pre-treatment baseline, but the steady-state V˙O2 remained reduced. Up to ∼4 weeks supplementation with 6 but not 3 mmol NO3− can reduce submaximal exercise V˙O2. A comparable reduction in submaximal exercise V˙O2 following chronic supplementation with 6 mmol NO3− can be achieved both with and without the acute ingestion of NO3− and associated elevation of plasma [NO2−]. •A low (3 mmol) and moderate (6 mmol) dose of nitrate (NO3−) elevated plasma nitrite concentration ([NO2−]) in a dose-dependent manner after 2 h, 7 days and 4 weeks of supplementation.•Submaximal exercise oxygen uptake (V˙O2) was unaffected by a low dose of NO3− after 2 h, 7 days and 4 weeks of supplementation.•A moderate dose of NO3− lowered submaximal exercise V˙O2 after 2 h (P = 0.06), 7 days and 4 weeks (both P < 0.05) of supplementation.•A reduction in V˙O2 was preserved 24 h after supplementation was stopped and plasma [NO2−] had returned to baseline.